2022
DOI: 10.1039/d2qo00395c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structures and fluorescence properties ofgem-linked cyclic tetraphenylethylenes and cyclic hexaphenylethylenes

Abstract: Rigid cyclic molecules are of great interest due to their intriguing structures and unique properties. Here, we report the facile synthesis of gem-linked cyclic tetraphenylethylenes and cyclic hexaphenylethylenes, namely [n]CTPEs...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…[8] In 2022, we successfully synthesized [n]gem-link cyclic tetraphenylethylenes ([n]g-CTPEs) (Figure 1c) and [n] gem-link cyclic hexaphenylethylenes ([n]g-CHPEs). [9] We found that the strain energy of [2]g-CTPE reached an impressive 256.06 • kJ mol À 1 and [2]g-CTPE emits intense blue light in both solution and aggregated states, exhibiting a dual-state luminescence phenomenon. As a continuous part of this research, we decided to synthesize the cis-connected cyclotetraphenylethylenes, namely [n]c-CTPEs (Figure 1d), and make comparisons on the structures and fluorescence properties of the cis-connected cyclic tetraphenylethylenes with the gem-linked tetraphenylethylene analogues.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…[8] In 2022, we successfully synthesized [n]gem-link cyclic tetraphenylethylenes ([n]g-CTPEs) (Figure 1c) and [n] gem-link cyclic hexaphenylethylenes ([n]g-CHPEs). [9] We found that the strain energy of [2]g-CTPE reached an impressive 256.06 • kJ mol À 1 and [2]g-CTPE emits intense blue light in both solution and aggregated states, exhibiting a dual-state luminescence phenomenon. As a continuous part of this research, we decided to synthesize the cis-connected cyclotetraphenylethylenes, namely [n]c-CTPEs (Figure 1d), and make comparisons on the structures and fluorescence properties of the cis-connected cyclic tetraphenylethylenes with the gem-linked tetraphenylethylene analogues.…”
Section: Introductionmentioning
confidence: 91%
“…We are interested in the synthesis and properties of highly strained molecules [8] . In 2022, we successfully synthesized [n] gem ‐link cyclic tetraphenylethylenes ( [n] g ‐CTPEs ) (Figure 1c) and [n] gem ‐link cyclic hexaphenylethylenes ( [n] g ‐CHPEs ) [9] . We found that the strain energy of [ 2] g ‐CTPE reached an impressive 256.06 ⋅ kJ mol −1 and [2] g ‐CTPE emits intense blue light in both solution and aggregated states, exhibiting a dual‐state luminescence phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…In 2022, Jiang and colleagues reported a series of tetraphenylethylene (TPE) containing macrocycles 49 ( i.e. , [ n ]CTPE 49 and [ n ]CHPE 50 ) (Fig.…”
Section: Carbon-rich Macrocycles As Potential Optical Materialsmentioning
confidence: 99%
“…[20][21][22] Tetraphenylethylene (TPE) is a star molecule of AIE materials, widely used due to its simple synthesis, modification, and unusual luminescence. [23][24][25][26][27][28][29][30][31][32][33][34][35][36] A series of eightshaped double macrocycles can be formed by connecting the benzene rings of TPE in pairs (Scheme 1). These structures have received great attention, leading to a series of studies on the AIE mechanism, ion recognition, and multicolor luminescence.…”
Section: Introductionmentioning
confidence: 99%